PENGARUH KONTINUITAS BELAJAR DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR DENGAN DIMODERASI OLEH PERSISTENSI DIRI (Survei pada Siswa dalam Mata Pelajaran Ekonomi Kelas X SMA Negeri 1 Cikatomas Tahun Ajaran 2023/2024) - Eci Mulyani; Ai Nur Solihat; Yoni Hermawan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The problem in this research is regarding low student learning outcomes. There are still many students who have not reached the minimum completeness criteria (KKM) determined by the school in economics subjects. The aim of this research is to determine the influence of learning continuity and achievement motivation on learning outcomes moderated by self-persistence. This research uses a survey method with an explanatory research design. The population in this study was class X students, totaling 420 people. The sampling technique used was a simple random sampling type probability sampling technique so that a sample of 205 people was obtained. Data collection methods use questionnaires and documentation. The data analysis technique uses multiple linear regression analysis and moderated regression analysis (MRA). The research results show that there is a partial and simultaneous influence between learning continuity and achievement motivation on learning outcomes. Then the results of moderated regression analysis (MRA) show that there is no moderating effect of self-persistence on learning continuity on learning outcomes, while it shows that there is a moderating effect of self-persistence on achievement motivation on learning outcomes.